Integrated Product Policy and Environmental Product Innovations: An Empirical Analysis - Katharina-Maria Rehfeld; Klaus Rennings; Andreas Ziegler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2004)
The European Commission has recently stepped up its promotion of the ?Integrated Product Policy?. The objective of the IPP is to support the realisation of environmental product innovations and thus to achieve a broad reduction of all environmental impacts throughout a product?s life cycle. Based on a unique company level data set for the German manufacturing sector, this paper empirically examines the relationship between environmental organisational measures regarded as IPP measures by the European Commission and environmental product innovations. According to the econometric analysis, the certification of environmental management systems has a significantly positive effect on environmental product innovations. Waste disposal measures or product take-back systems appear to be an even more important driver of environmental product innovations. The econometric analysis also shows that other factors that have been suggested in the literature, such as environmental policy, technology push and market pull, as well as other specific company characteristics have a significantly positive influence on environmental product innovations. According to the descriptive analysis of environmental product innovators, economic aspects (i.e. higher prices) rather than soft factors appear to be the major obstacles to the commercial exploitation of environmental products and thus also to environmental product innovations.
Keywords: Q01; C25; O32; Q55; O33; 330; Integrated Product Policy; Product Innovation; Environmental Innovation; Innovation Management; Technological Innovation; Discrete Choice Models; Umweltmanagement; Innovation; Umweltverträgliches Produkt; Produktpolitik; Schätzung; Verarbeitendes Gewerbe; Deutschland